Single‐phase rectifier circuit with output voltage enhancement for automotive generators. Issue 3 (1st September 2015) - Al‐Busaidi, Ahmed; Pickert, Volker; Gadoue, Shady
Abstract : This study presents a new concept for single‐phase diode bridge rectifier circuits applied to automotive applications. The proposed circuit is able to enhance the output voltage to a much higher output level over a wide load range compared to the classical single‐phase diode bridge rectifier without using complex control algorithms. This is achieved by embedding two capacitors and two switches to a new designed diode bridge converter topology. The embedded capacitors are charged and discharged simultaneously with the help of two switches. The embedment of the capacitors and switches will provide two functions: energy storage as known from traditional rectifier circuits and voltage oscillation with the supply inductance to reduce supply current distortion. The switches are on/off event triggered and do not require any complex control algorithms. The operation and the performance of the proposed rectifier are simulated using Matlab/Simulink software. Experimental results are obtained from a 1 kW prototype test circuit, which is used to evaluate the performance of the proposed circuit. Test results show a significant increase in the output voltage in addition to a reduced supply current distortion.